Endoluminal Vacuum Therapy for Ivor Lewis Anastomotic Leaks: A Pilot Study in a Swine Model - Scott, RB; Ritter, LA; Shada, AL; Feldman, SH; Kleiner, DE (Clinical and translational science, 2017)
Anastomotic leaks are a serious complication associated with Ivor Lewis esophagectomies. Endoluminal negative pressure vacuum devices create a possible treatment alternative to conventional surgical intervention. Ten pigs had an intrathoracic esophageal anastomosis with a 1‐cm defect. The experimental group had the device placed intraoperatively across the defect, whereas the control group did not. Once treatment was completed, a contrast fluoroscopic study and necropsy was performed. All control pigs had contrast extravasation on fluoroscopy and contamination on necropsy. The experimental group had no radiologic leak and no contamination on necropsy. The P value for leak is 0.03. This study demonstrated that endoluminal negative pressure vacuum therapy is tolerated in the swine model and is successful in facilitating the healing of anastomotic leaks. Endoluminal negative pressure vacuum therapy has potential clinical benefits, including decreased morbidity and length of hospital stay.